2005
DOI: 10.1080/10807030590949654
|View full text |Cite
|
Sign up to set email alerts
|

A Spatially Explicit Model of the Wild Hog for Ecological Risk Assessment Activities at the Department of Energy's Savannah River Site

Abstract: In North America, wild hogs (Sus scrofa) are both sought after as prime game and despised due to their detrimental impacts to the environment from their digging and rooting behavior. They are also a potentially useful indicator species for environmental health for both ecological-and human-based risk assessments. An inductive approach was used to develop probabilistic resource selection models using logistic regression to quantify the likelihood of hogs being in any area of the Department of Energy's 805 km 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Although N. taxispilota were excluded from the exposure analysis due to sample size limitations, their diet, which consists almost exclusively of fishes (Mills et al 1995), bolsters the inference that fish may not be the vector for U or Ni exposure in Tim's Branch. This parallels exposure assessments conducted for wild hogs (Sus scrofa) for Tim's branch showing that both Ni and U exposure was related to diet (Gaines et al 2005). The Agency for Toxic Substances and Disease Registry (ATSDR) has derived a minimal risk level (MRL) for soluble compounds of U of 0.002 mg/kg/day based on the lowest observed adverse effect level (LOAEL) of 0.05 mg/kg/day for renal effects in rabbits (ATSDR 1999;Gilman et al 1998).…”
Section: U and Ni Exposurementioning
confidence: 99%
“…Although N. taxispilota were excluded from the exposure analysis due to sample size limitations, their diet, which consists almost exclusively of fishes (Mills et al 1995), bolsters the inference that fish may not be the vector for U or Ni exposure in Tim's Branch. This parallels exposure assessments conducted for wild hogs (Sus scrofa) for Tim's branch showing that both Ni and U exposure was related to diet (Gaines et al 2005). The Agency for Toxic Substances and Disease Registry (ATSDR) has derived a minimal risk level (MRL) for soluble compounds of U of 0.002 mg/kg/day based on the lowest observed adverse effect level (LOAEL) of 0.05 mg/kg/day for renal effects in rabbits (ATSDR 1999;Gilman et al 1998).…”
Section: U and Ni Exposurementioning
confidence: 99%
“…Different species provide different correlations with landscape metrics depending on their landscape preferences, i.e., large compact patches are preferred by wild hogs (Gaines et al, 2005), moose (Maier et al, 2005), deer (Table 1; Foster et al, 1997;Plante et al, 2004) and possums (Eyre and Buck, 2005), while ocelots (Jackson et al, 2005) and gliders (Table 1; McAlpine and Eyre, 2002) preferred areas that had a greater degree of fragmentation (i.e., a larger number of patches of smaller size, and with more edge).…”
Section: Biodiversity and Habitat Analysismentioning
confidence: 99%
“…Landscape metrics have been used to determine the landscape preferences of raccoons (Henner et al, 2004), gray wolves (Mladenoff et al, 1995), wild hogs (Gaines et al, 2005); moose (Maier et al, 2005), deer (Foster et al, 1997;Finder et al, 1999;Kie et al, 2002), black bears (Kindall and Van Manen, 2007), ocelots (Jackson et al, 2005), elk (Stubblefield et al, 2006), possums (Eyre and Buck, 2005) and bats (Limpert et al, 2007). Different species provide different correlations with landscape metrics depending on their landscape preferences, i.e., large compact patches are preferred by wild hogs (Gaines et al, 2005), moose (Maier et al, 2005), deer (Table 1; Foster et al, 1997;Plante et al, 2004) and possums (Eyre and Buck, 2005), while ocelots (Jackson et al, 2005) and gliders (Table 1; McAlpine and Eyre, 2002) preferred areas that had a greater degree of fragmentation (i.e., a larger number of patches of smaller size, and with more edge).…”
Section: Biodiversity and Habitat Analysismentioning
confidence: 99%
“…To accomplish this, the U, Ni, and Hg concentrations and bioavailability in lower trophic level biota from seven beaver impounded ponds were quantified with a focus to determine their transport potential within the Tims Branch food web. These three COPC metals are used because previous studies in this system have shown they pose the most risk to both plant and animal species inhabiting or potentially consuming biota from this system (Batson et al 1996;Chow et al 2005;Gaines et al 2005;Murray et al 2010;O'Quinn 2005;Punshon et al 2003a,b;Sowder et al 1996, SRNS 2011. Specifically, studies have shown an increase of 1500-2800% of U transported through SRS tributaries during storm events when compared to base flow measurements indicating that U is still present in the aquatic systems even though it may not be as mobile (Batson et al 1996;Buettner et al 2011).…”
Section: Rationalementioning
confidence: 99%
“…This study utilizes the most current data available to examine trophic transfer and how U, Ni, and Hg concentrations in water, Anuran and Anisopteran larvae, biofilms, and detritus samples compare to established action limits. We chose these taxa, because of unanswered questions left from previous studies examining higher trophic positions as well as sediment and plant tissue pathways in this system (Batson et al 1996;Chow et al 2005;Gaines et al 2005;Murray et al 2010, O'Quinn 2005Punshon et al 2003a,b;Sowder et al 1996). Specifically, TFs were calculated as an index of change in U, Ni, and Hg trace metal concentration within and between lower trophic levels.…”
Section: Introductionmentioning
confidence: 99%